Green Practices in Northern Region Hotels of Malaysia - Amran, Noor Afza; Saad, Natrah; Aripin, Norhani (GATR Enterprise, 2017)
The objective of this paper is to examine green practices of hotels located in Northern region of Malaysia. The sample of the study is 115 hotels in Penang, Kedah and Perlis. Questionnaires were personally delivered to each respective hotel. The response rate for the survey is 43%. Findings from the survey indicate that hoteliers have started to show a positive sign towards adoption of green practices such as usage of power saving bulbs, water conservation, and recycling management program. However, more campaigns on awareness and the benefits of green practices need to be said aloud. It will indirectly educate the hoteliers and society at large on the importance of saving the Mother Nature.